A szervezeti kultúra változásának hatása a Kőrösi Csoma Sándor Kőbányai Kulturális Központban - Farkas-Gáll Gizella (2016)
As the subject of my paper I chose the effect of the change of the organizational culture in the Kőrösi Csoma Sándor Cultural Centre, which is changing and modifying itself according to the market and budgetary environment, in order to achieve more effective and more economical operation. As the title of my paper indicates, I have analysed models of organizational culture that follows the integration of a unit of public education, using, in addition to my own personal experience, specialized literature available. Analysing various theories I put forward statements and then I attempt to confirm them with a questionnaire. I also keep in mind the differences and divergences in theories. I determine these assumptions in relevance to the workings of public education. I believe it is important to underline a number of organisational culture theories, since only the sum of these theories can provide me with a clearer, more complete and authentic picture of the effect the change of culture has on operation. I give a detailed picture of the establishment of the institute, of its predecessor, the Pataki Cultural Centre, and of the Köbánya Children and Youth Leisure Centre, which was integrated into the former, and which have undergone continuous change in the last 20 years. The organisational change, the setting up of the new institute was brought about by the market and legal environment. After this I will present the relevant legal instruments affecting public education, its obligations as set forth in the founding document. Colleagues working here carry out the public education tasks of the Self-Government, and provide for market requirements. The restructuring brought about major changes in the structures, the operation and the organizational culture of the institutions. Responding to the measures that provide for the reduction of divisions and the simplification of the processes, the public education institute changed its character gradually, and the „customer-oriented” philosophy came to the forefront, together with efficiency and economy as the desirable directions for development. I have worked out a questionnaire built on the value-dimensions of organisational culture, which was completed by 29 colleagues. I arrived at my conclusions by analysing and collating the results of the questionnaire. I have established my findings by analysing and collating the results of the questionnaires. This helped to show and highlight nexi which have caused major changes in the organisational culture after reorganisation. In view of the results I put forward recommendations to facilitate the development of organizational culture and more effective operation.